The Efficacy of Blue Light in Decreasing Physiological Fear Responses - Muhammad, Kamilah (My University, 2024)
Mental health issues involving the psychological concept of fear conditioning are rapidly increasing in prevalence among today’s society. Fear conditioning commonly affects individuals in the form of GAD, PTSD, and specific phobias. Specific phobias elicit irrational fear in individuals when there is no apparent threat present. Specific phobias can decrease an individual’s quality of life by preventing them from engaging in activities and occupying certain environments. Blue light has been found to increase serotonin levels, which are relatively low in individuals exhibiting anxiety. The purpose of this study was to determine if blue light therapy decreased physiological fear responses in individuals experiencing specific phobias. Using ECG, respiration, and pupil dilation an individual’s physiological fear response was measured upon exposure to a fear-inducing stimulus. Blue light therapy was then administered for 30 minutes, and physiological readings were collected a second time. Final analysis was conducted utilizing t-test methods. Blue light was found to be effective in deceasing pupil dilation for all participants, however, its efficacy for vascular measures was only found in female participants. Nitric oxide sensitivity in males may account for differing results.
Keywords: Blue light; virtual reality; fear; heart rate; respiration; nitric oxide